The Impact of tourism on the socio-cultural life of the community and the environment in The Prai Ijing Traditional Village East Nusa Tenggara - Muhammad Deo Zidane H; Ulfi Maranisya (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2024)
Purpose: This study aims to identify the impact of tourism on the socio-cultural life of the community and the environment in Prai Ijing Traditional Village. Method: This study used descriptive qualitative methods and triangulation analysis of data sources. The data collection techniques used were observations in Prai Ijing Traditional Village, interviews with 7 informants representing the village government, Pokdarwis, and community leaders, and literature studies. The 7 informants are representatives of the Prai Ijing Traditional Village who felt the impact of tourism activities and were directly involved in the process of managing tourism activities in the Prai Ijing Traditional Village. From the pioneering stage to becoming a developed tourist village. The informant selection method uses Purposive and Snowball Sampling methods with Miles and Huberman data processing techniques. Result: The results of this study show that tourism in Prai Ijing Traditional Village has a positive impact on socio-cultural and environmental life. In the Socio-culturally dimention, people increasingly preserve cultural values and see tourism as a factor in maintaining traditions, while tourism activities also increase public awareness of environmental cleanliness and appearance without harming cultural values and traditions. In terms of the environment, tourism development in the village contributes positively to environmental conservation and arrangement, showing the community's ability to maintain stability and environmental preservation despite tourism growth. Contribution: This research contributes to determining the impact of tourism activities on the socio-cultural life of the community and the environment in Prai Ijing Traditional Village so that the community can realize and take preventive actions from potential negative impacts that can occur.